Tariff substitute for rules of origin in free trade areas. - LLOYD, P.J. (1993)
Discusses the problems of trade deflection, and the treatment of the rules of origin in practice in some free trade areas, particularly the EFTA, NAFTA, and the Closer Economic Relations (CER) Agreement between Australia and New Zealand. Proposes a value added tariff which could substitute for all rules of origin.